2017
DOI: 10.1007/s10545-017-0067-x
|View full text |Cite
|
Sign up to set email alerts
|

Rigor of non‐dairy galactose restriction in early childhood, measured by retrospective survey, does not associate with severity of five long‐term outcomes quantified in 231 children and adults with classic galactosemia

Abstract: One of many vexing decisions faced by parents of an infant with classic galactosemia (CG) is how carefully to restrict non-dairy galactose from their growing child’s diet. Until recently, many experts recommended vigorous lifelong dietary restriction of milk and all high-galactose dairy products as well as some non-dairy sources of galactose such as legumes and specific fruits and vegetables. Recently, experts have begun to relax their recommendations. The new recommendations, that restrict only high galactose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 23 publications
3
25
1
Order By: Relevance
“…The socioeconomic status of patients could have a significant effect on clinical outcomes (Shulman et al 1991;MacDonald et al 2010;Stockler et al 2012) and this was not formally assessed in our study. However, a recent study of 231 patients with classic galactosemia (Frederick et al 2017) showed no association between family income or parent education level and rigor of child dietary galactose restriction as well as between rigor of non-dairy galactose restriction and long-term outcomes, including growth. The majority of galactosemia females ≥15 yo in group 2 exhibited varying degrees of ovarian function impairment from menstrual irregularities to premature ovarian insufficiency/infertility, and demonstrated abnormal levels of reproductive hormones including AMH (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The socioeconomic status of patients could have a significant effect on clinical outcomes (Shulman et al 1991;MacDonald et al 2010;Stockler et al 2012) and this was not formally assessed in our study. However, a recent study of 231 patients with classic galactosemia (Frederick et al 2017) showed no association between family income or parent education level and rigor of child dietary galactose restriction as well as between rigor of non-dairy galactose restriction and long-term outcomes, including growth. The majority of galactosemia females ≥15 yo in group 2 exhibited varying degrees of ovarian function impairment from menstrual irregularities to premature ovarian insufficiency/infertility, and demonstrated abnormal levels of reproductive hormones including AMH (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…A sample size of 32 (patients 3F and 6M excluded) with an allocation ratio of 1.9 between group 1 and group 2 was adequate to produce 80% power to detect a mean difference in the proportion of galactosemia patients with a negative long-term outcome of 0.55 (conservative estimation based on (Schweitzer et al 1993;Jumbo-Lucioni et al 2012;Frederick et al 2017) withanalphaof0.01inatwo-sidedanalysis.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated Gal-1-P is a known competitive substrate for inositol monophosphatase 1 (IMPase1) and various glycosyltransferases and also inhibits UDP-hexose pyrophosphorylases [ 6 , 12 ]. In addition, over-restriction of galactose in the long-term may contribute to the disease phenotype by further depleting UDP-galactose in susceptible individuals, potentially disrupting glycosylation dependent pathways [ 13 , 14 ]. Down-regulation of the key P13K/Akt signalling pathway has also been recently reported in the GALT deficient mouse model [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Primary ovarian insufficiency (POI) is one of the most common long-term complications associated with classic galactosemia (CG), impacting a large majority of girls and women with CG despite early detection (Fridovich-Keil et al 2011; Berry 2014) and careful lifelong dietary restriction of galactose (Frederick et al 2017). Details of the presentation and progression of POI in CG have remained unclear, however, as has clarification of a useful prognostic marker for this outcome (Welling et al 2017).…”
Section: Introductionmentioning
confidence: 99%